Color and flavor stability of beef gluteus medius as influenced by postmortem aging time and blade tenderization - Dietz, Garret (Kansas State University, 2014)
A total of 45 top sirloin butts (IMPS 184) were procured from three commercial beef processing facilities to determine the effects of post-mortem aging time and blade tenderization on the quality of beef gluteus medius (GM) steaks. Top sirloin butts were randomly assigned to five post-mortem aging periods (5, 19, 33, 47, and 61 days). One-half of each beef GM was randomly assigned to either a blade tenderized treatment or a non-blade tenderized treatment that was not blade tenderized. Steaks were then evaluated for thiobarbituric acid reactive substances (TBARS), metmyoglobin reducing activity (MRA), oxygen consumption rate (OCR), visual color panel, instrumental color, Warner-Bratzler shear force (WBSF), Lactic Acid Bacteria (LAB) enumeration, pH, and sensory properties. Aging × blade tenderization interactions (P < 0.05) were found for display color panel, discoloration panel, WBSF, overall tenderness, myofibrillar tenderness, bloody/serumy, metallic, overall sweet, and bitter (P < 0.05). As steaks were aged longer and blade tenderized they became more discolored during display and more tender. In addition, there were aging × display time interactions (P < 0.05) observed for L*, a*, b*, display color panel, and discoloration panel. As steaks were aged longer, they had increased L*, a*, b*, and hue angle values and display color panel scores when initially put into a retail case, but L*, a* and b* decreased and discoloration scores increased as display time increased. Furthermore, there were blade tenderization × display time interactions (P < 0.05) found for display and discoloration panels. Blade tenderized steaks discolored faster in retail display than non-blade tenderized steaks. With increased aging time, there was an increase (P < 0.05) in TBARS, OCR, initial color panel, LAB enumeration, and warmed-over flavor, as well as a decrease in MRA. Also, as aging increased there was a decrease (P < 0.05) in MRA, initial color panel scores, and WBSF values. Blade tenderization significantly increased (P < 0.05) initial color panel scores, rancid flavor, and spoiled flavor. Increasing the aging time of the GM, produced steaks with decreased color stability, altered the flavor profile, and increased tenderness. Blade tenderization significantly increased tenderness, increased discoloration in a retail case, and produced more undesirable flavors.
Keywords: Beef; Gluteus medius; MRA; OCR; ColorPostmortem aging; Animal Sciences (0475)